Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ijms24021800
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Permeation Studies in Rat Brain of Natural Compounds Led to Investigate Eugenol as Direct Activator of Dopamine Release in PC12 Cells

Abstract: Eugenol, cinnamaldehyde and D-limonene, the main components of natural essential oils, are endowed with antioxidant and anti-inflammatory properties which allow them to induce beneficial effects on intestinal, cardiac and neuronal levels. In order to characterize their pharmacokinetic profiles and aptitude to permeate in the central nervous system after intravenous and oral administration to rats, new analytical procedures, easily achievable with HPLC-UV techniques, were developed. The terminal half-lives of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The effective dose of eugenol that can be traced from the reported studies is around 25–100 mg/kg per oral treatment in AD and PD animals (Garabadu & Sharma, 2019; Vora et al, 2022). Although the oral bioavailability of eugenol is reported to be poor, this compound is suggested to bear good BBB permeability and demonstrated as an efficient therapeutic agent with no reported toxicity (Barot & Saxena, 2021; Pavan et al, 2023; Pramod et al, 2010; Ulanowska & Olas, 2021). Eugenol is reported to exert antioxidative effects, reduce mitochondrial dysfunction, inhibit AChE activity and restore brain ACh content and improve memory functions in rat models of AD (Garabadu & Sharma, 2019; Liu, Niu, et al, 2013; Liu, Wang, et al, 2013).…”
Section: Phyto‐compounds and Their Neuroprotective Effects In Ad And ...mentioning
confidence: 99%
“…The effective dose of eugenol that can be traced from the reported studies is around 25–100 mg/kg per oral treatment in AD and PD animals (Garabadu & Sharma, 2019; Vora et al, 2022). Although the oral bioavailability of eugenol is reported to be poor, this compound is suggested to bear good BBB permeability and demonstrated as an efficient therapeutic agent with no reported toxicity (Barot & Saxena, 2021; Pavan et al, 2023; Pramod et al, 2010; Ulanowska & Olas, 2021). Eugenol is reported to exert antioxidative effects, reduce mitochondrial dysfunction, inhibit AChE activity and restore brain ACh content and improve memory functions in rat models of AD (Garabadu & Sharma, 2019; Liu, Niu, et al, 2013; Liu, Wang, et al, 2013).…”
Section: Phyto‐compounds and Their Neuroprotective Effects In Ad And ...mentioning
confidence: 99%
“…Polyphenols, or the main components of essential oil, often appear able to permeate the brain from the bloodstream and are promising agents against neurodegenerative diseases. On the other hand, their fast elimination from the body compromises their use as therapeutic agents [ 12 , 13 , 20 , 21 , 22 , 23 , 24 ]. Co-administration forms and the development of prodrugs designed as conjugates with biocompatible molecules appear promising methods to obtain innovative nanocarriers that are able to cross the BBB and to deliver phytochemicals to the brain, thus strengthening their therapeutic effects.…”
Section: Innovative Formulations Designed To Enhance the Central Effe...mentioning
confidence: 99%
“…The antioxidant and anti-inflammatory properties of polyphenols, one of the major categories of phytochemicals, contribute to these compound beneficial effects by modulating the activation of cytokines and regulating the gene expression of pro-inflammatory molecules [ 1 ]. Essential oils are other phytochemicals characterised by antioxidant and anti-inflammatory properties [ 8 ], and are potentially beneficial at both peripheral [ 9 , 10 ] and central levels [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group recently found that eugenol administered orally or intravenously to rats is able to efficiently cross the blood-brain barrier. Moreover, in differentiated PC12 cells, an in vitro model that mimics PD because these cells synthesize and store catecholamines and dopamine, eugenol treatment increased cell survival and enhanced dopamine secretion [49]. Eugenol was also tested in a mouse model of PD based on the i.p.…”
Section: Essential Oils and Neurodegenerative Diseasesmentioning
confidence: 99%